Demystifying re-emergence zoonotic threat: A 5-year epidemiology of leptospirosis in Negeri Sembilan, Malaysia - Mohd ‘Ammar Ihsan Ahmad Zamzuri; Sharina Mohd Shah; Norjeehan Junadi; Muazz Auzzaie Abd Latif; Khairul Aiman Rosly; Farah Nabila Abd Majid; Rahmat Dapari; Massitah Mihat; Siti Salwa Ibrahim; Muhammad Ismail; Suriyati Abd Aziz; Mohd Rohaizat Hassan; et al. (Clinical Epidemiology and Global Health, 2023)
Introduction: Leptospirosis is a re-emergence of zoonotic disease with significant morbidity and mortality. As a tropical country, there is a concerning trend of leptospirosis infection in Malaysia. However, the epidemiological study of the infection remains scarce and does not reflect the current information. Therefore, the study aimed to describe its epidemiology within the last 5-year in the state of Negeri Sembilan. Methods: A cross-sectional study was done using dataset from national electronic surveillance registry from year 2018–2022. Descriptive statistics method was applied to build the epidemiological narrative of leptospirosis infection. All data was kept confidential and abide to Helsinki declaration. Results: A total of 1290 cases of leptospirosis was registered and included in the analysis. Majority of the cases were from adults’ group (68.4 %), male (68.4 %), of Malay ethnicity (69.8 %), unemployed (56.7 %), and from rural area (54.4 %). The possible risk exposure was from rat infestation (15.1 %), water-based activity (12.5 %), and contact with contaminated soil (7.7 %). The proportion of cases registered in the densely populated areas were comparable among those who are employed and unemployed There were overall 21 (1.6 %) mortality cases from the data. Conclusion: Leptospirosis is a public health threat and need to be approached holistically. Awareness of the disease need to be continuously advocated to the public as well as to the healthcare providers. Strengthening the surveillance system at the local and national level is important as it can act as an early warning system to prevent outbreak to happen.